P408 Intestinal failure in Crohn's disease: A case–control study. (16th January 2018) - Soop, M; Bond, A; Nixon, E; Teubner, A; Abraham, A; Carlson, G; Lal, S
Abstract: Background: Although intestinal failure (IF) is a feared complication in Crohn's disease (CD), risk factors, direct causes and outcomes of this complication have not been well described. Methods: Consecutive patients with CD admitted to a national intestinal failure unit between 2000 and 2010 were identified from prospective database. Patients with IF were matched for age and sex to control CD patients without IF. Details of surgical and medical management were collected from clinical records. The event leading to and outcomes of IF was assessed in each case. Baseline and surgical risk factors for IF were further assessed by univariable comparison. Results: Sixty-nine patients with CD were admitted with IF. All had undergone recent abdominal surgery. The direct cause of IF was abdominal septic complications in 39 (56%) (anastomotic dehiscence in 24, enteric fistulation in 12 and intra-abdominal abscess in 3), uncomplicated bowel resection in 26 (38%) and proximal small-bowel stoma in 4 (6%). Of 24 patients with anastomotic dehiscence, the anastomosis had been formed during corticosteroid therapy in 9 and during an emergency procedure in 5. Sixty-nine matched controls were selected. At CD diagnosis, IF patients were younger than controls (25 (8–85) vs. 32 (13–67) years, p 0.025)); fewer had colonic disease (11 of 69 vs. 35/69, p < 0.0001); and more had stricturing phenotype (49 of 69 vs. 14 of 69, p < 0.0001). More IF patients than controls had had previous abdominal surgery (69 of 69 vs. 29 of 69, p < 0.0001). Compared with the 29 controls who had surgery, IF patients had undergone more laparotomies (3 (1–7) vs. 2 (1–6), p < 0.0001)) and more had severe postoperative complications (45 of 69 vs. 2 of 29, p < 0.0001). Thirty-seven of 69 IF patients subsequently had reconstructive surgery; 23 regained nutritional autonomy. Conclusions: IF is a severe complication of CD, with two-thirds of patients remaining on parenteral nutrition. The most frequent event leading directly to IF was a septic complication following abdominal surgery, in many cases following intestinal anastomosis in the presence of significant risk factors such as corticosteroid therapy or emergency surgery. IF in CD was associated with younger onset of CD, small-bowel location, stricturing phenotype, and disease requiring more abdominal procedures. A reduced need for abdominal surgery, an increased awareness of risk factors for abdominal septic complications and pre-operative optimisation may reduce the incidence of IF in CD.